2022
DOI: 10.1007/s11340-022-00839-5
|View full text |Cite
|
Sign up to set email alerts
|

A Deconvolution Method for the Mapping of Residual Stresses by X-Ray Diffraction

Abstract: Background Inherent averaging effects in X-ray diffraction measurement of residual stresses, related to the finite size of the irradiated area, lead to inaccurate measurements in the presence of high surface stress gradients. Objective This paper develops a reconstruction method which allows the mapping of heterogeneous residual stresses from X-ray diffraction averaged measurements. Methods The stress reconstruction is based on a deconvolution of the average XRD measurements. The combination of a fine measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…119,121) Other works have focused on the simulation of fracture or residual stress in RCS-processed multimodal materials. 120,[127][128][129]…”
Section: Repetitive Corrugation and Straightening (Rcs)mentioning
confidence: 99%
“…119,121) Other works have focused on the simulation of fracture or residual stress in RCS-processed multimodal materials. 120,[127][128][129]…”
Section: Repetitive Corrugation and Straightening (Rcs)mentioning
confidence: 99%
“…They compared the results with the drilling method, and found that the residual stress on the surface of the lampshade tested by the two methods was very close. Tajdary et al [7] considered the inherent mean effect in residual stress X-ray diffraction (XRD) measurements, which is related to the finite size of the irradiation area, resulting in inaccurate measurements in the presence of high surface stress gradients. A deconvolution stress reconstruction method based on average XRD measurements was proposed, which allowed for the drawing of non-uniform residual stress maps based on XRD measurements.…”
Section: Introductionmentioning
confidence: 99%